Antecedent Energizing Profesional Networks And Marketing Performance Fashion Industry: Conceptual Framworks And Research Proposition - Riyoko, Sisno; Hendar, Widodo (Technium Social Sciences Journal, 2023)
Many studies on the connection between an entrepreneurial mindset and business performance were conducted in the preceding year. As a result, this study puts forth a fresh notion that sets it apart from the competition: the necessity of professional networks for reviving the link between entrepreneurial orientation and marketing efficiency. This study seeks to understand the relationships between three dimensions of entrepreneurial orientation—being proactive, taking risks, and being innovative and the marketing success and thriving professional networks of Indonesian fashion SMEs. The process's output is the energization of professional networks based on a synthesis of the theories of dynamic marketing capabilities and achievement goals. A single informant survey of Fashion SMEs owners in the relevant domain using structural equation modeling (SEM) and a moderator test is the suggested methodology for testing the proposed model. While the study's statistical population including all business owners of Indonesian fashion SMEs. Purposive sampling was employed in this investigation, with a sample size of 250 respondents. All respondents received questionnaires, which were then used as the primary data collection tool. The paper finishes with recommendations and lines of inquiry for additional study.